Brief History of Scientific Interpretation Approach and Some Studies on This Topic - DEMİRCİ, Mehmet (Scientific Journal of Faculty of Theology, 2021)
It has been criticized by many circles as well as by the defenders of the scientific Qur’an interpretation approach. Some of these criticisms are based on the limited level of knowledge and culture of the interlocutors at the time the Qur’an was revealed. They argue that it would not be the right approach to attribute meaning to the verses based on the sciences that emerged in the later period. Some criticisms have also focused on the fact that scientific exegesis has been developed with a defensive understanding as a result of the domination of Western civilization over Muslims. The purpose of this study is to point out the historical roots of scientific exegesis and to draw attention to the fact that this approach should not be sacrificed to the defensive attitude that emerged in the modern period.